Nurses’ Perception on Evidence-Based Practice in Tertiary Hospital of Nepal - Bhandari, Bhagwati; Karki , Sabita; Lamichanne, Narayani; Maharjan, Purna Devi; Aryal , Sharada (Journal of Karnali Academy of Health Sciences, 2024)
Background: The evidence-based practice movement has spread globally, prompting calls for evidence-based policymaking and public health. Health care being the dynamic discipline with research, is, intended to improve practice through evidence-based novel approaches. Nurses must use evidence-based practice (EBP) in order to raise the standard of care; limited evidence are available in Nepal. This study aimed to assess the perception of evidence-based practice among nurses of a tertiary hospital in Nepal. Methods: A quantitative cross-sectional study was conducted among the 100 nurses of Bir Hospital in Kathmandu. The self administered questionnaire was applied using the Evidence Based Practice Questionnaire (EBPQ). A purposive sampling technique was employed. Mean score was calculated to assess the nurses’ perceptions in the three sub-scales of knowledge, attitude, and use of evidence-based practice. Bivariate analysis was performed to examine the relationship between subscales. Results: Majority (89.0%) of nurses did not receive training on evidence-based practices. The mean score of knowledge on EBP was 4.47±1.11, the mean score of attitudes on EBP was 4.45±1.06, and the mean score of EBP use was 4.18±1.42. The knowledge, attitude, and use of EBP were not significantly associated with the selected demographic variables (age, work experience, EBP training and marital status). Conclusion: Findings of the study indicates that implementation of EBP use needs to be strengthened among the nurses. Nurses need to be more involved in the implementation of EBP. To incorporate evidence in practice, nurses require training, incorporating EBP into nursing curricula and enhancing support from high authorities.